Implementasi Algoritma Rete pada Sistem Pakar Untuk Mendeteksi Autism Spectrum Disorder Berbasis Web - Kevin, Kevin; Hansun, Seng (JIK: Jurnal Ilmu Komputer, 2015)
Autism is a very complex developmental disorder in children. According to data that was acquired from Centers for Disease Control and Prevention (CDC), 1 in every 68 children suffers from Autism Spectrum Disorder. This, of course needs proper handling from pa-rents and professionals. Therefore a web based expert system application is made to predict the type of Autism Spectrum Disorder according to the most updated international standards. This application is made using Rete Algorithm. Based on the test using 31 data, all of system output matches the results issued by real human experts.Keywords: index termsÃ¢â‚¬â€autism, autism spectrum disorder, expert system